Optimalisasi Literasi Digital untuk Meningkatkan Pemahaman Teknologi Informasi dan Kemampuan Identifikasi Hoax pada Siswa Sekolah Menengah Atas - M. Ari Prayogo; Febri Ramanda; Kharisma Kharisma (JPM: Jurnal Pengabdian Masyarakat, 2026)
The development of information technology and social media facilitates the dissemination of information, but also increases the risk of spreading fake news or hoaxes among students. Low digital literacy skills make students vulnerable to receiving and spreading information without first verifying it. This Community Service activity aims to increase students' understanding of the dangers of hoaxes, improve digital literacy skills, and train information verification skills using digital technology. The partners in this activity were 86 grade 10 students of SMA Negeri 1 Bontang. The activity was implemented through educational seminars, interactive lectures, discussions, case simulations, and direct practice using the Google Lens and Gemini applications for technology-based fact-checking. The activity was carried out for two days, namely on September 8-9, 2025. The level of activity success was measured through participant observation, pre- and post-tests, and participant reflections after the activity. The results of the activity showed an increase in students' understanding of the meaning of hoaxes, the characteristics of false information, and the importance of digital literacy in the use of social media. In addition, students were able to practice using Google Lens and Gemini to verify information independently. This activity also had a positive impact on changing students' attitudes, encouraging them to be more critical, wise, and responsible in receiving and disseminating digital information. Therefore, digital literacy-based anti-hoax education can be an effective way to foster a healthy digital culture among students.